Investigating Self-Awareness and Speaking Ability Correlations in Secondary EFL Education - Nurmiati, Nurmiati; Putri, Andi Mega Januarti; Junaedi, Ahmad (Innovations in Language Education and Literature, 2024)
This study investigates the correlation between self-awareness and English-speaking ability among second-grade students at SMAN 3 Majene, Indonesia. Employing a quantitative correlational design, the research examined 17 students selected through cluster random sampling from a population of 51. Data were collected using a self-awareness questionnaire assessing emotional awareness, self-assessment, and self-confidence, alongside a speaking ability test. Results revealed high levels of self-awareness among participants, with most reaching the "permanent" level, indicating strong self-reflection capabilities. Speaking abilities were predominantly rated as "good." However, statistical analysis showed a weak correlation between self-awareness and speaking ability, challenging the assumption of a direct link between these variables. This finding suggests that while self-awareness may contribute to internal motivation, it does not automatically translate to enhanced speaking performance in this EFL context. The study highlights the need for comprehensive pedagogical strategies that complement self-awareness development with targeted language instruction to improve EFL speaking skills effectively.